STRATEGI INDIA DALAM MENGHADAPI TIONGKOK TERKAIT SENGKETA PERBATASAN DI PEGUNUNGAN HIMALAYA TAHUN 2020 - Riski Wasiah Aulia Romadani; Ahmad Fuadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
One of the cases of border disputes is the border dispute between India and China in the Himalayas. Unlike the previous dispute cases which were resolved by peaceful diplomacy, in the incident in 2020 India began to Show several strategies to deal with China along the border in the Himalayas. This study uses a Neorealism perspective approach using the theory of Teritorial Dispute Resilience. The research and analysis method used in this study is a descriptive qualitative method with data collection techniques namely secondary data, through data collection by researchers and literature studies from various sources such as books, journals, official websites and several credible mass media. The results of this study indicate that India in dealing with China related to border disputes that occurred in 2020, has implemented several strategies according to the first option in the theory of teritorial dispute resilience. Namely, increasing military strength in border areas, strengthening military cooperation with the United States, increasing cooperative relations with QUAD, and implementing economic sanctions against China, which are strategies that are implemented to show its seriousness regarding restoring the status quo in border areas.Keywords: Defense Strategy, Border Dispute, LAC, QUAD.